Evaluation of the Compressive Strength of the Clay Soil Reinforced with the Column of Oil Palm Shell Concrete - Agus Muntohar, Y.Kusumahadi, RM.N. Barus (Fakultas Teknik Sipil Kasetsart University, 2015)
Application of the concrete from palm oil waste for soil improvement has not yet investigated. In this paper, the concrete made of PKS, sand, cement, and POFA mixtures was applied to form a column-reinforce clay soil system. The objective of this paper was to evaluate the compressive strength of the OPS concrete column reinforce clay soil. The soil specimens were compacted in a cylindrical steel mold with an inside diameter of specimen size was 125.4 mm diameter and 108 mm in height. The water content was varied into three i.e. near OMC, below OMC (optimum-dry), and above OMC (optimum-wet). The hole of 50.8 mm in diameter and 108 mm in height was made and filled with OPS concrete to form a column. The composition of the concrete mixture was 125 g of cement, 215 g of sand, 130 g of OPS, and 10 g of POFA. Cement and POFA was the binder in the mixture. The water to binder ratio (wbr) was 0.80 which was determined by trivial. It was concluded that the compressive strength has a tendency to increase with increases in moisture content of the soil. The highest compressive strength was obtained at optimum-wet moisture content that is 1736 kPa. The compressive strength increases with increasing the age of specimen. The compressive strength increases from 348 kPa (at 1 day) to 1736 kPa after 28 days of curing.